Business Marketing Planning At Simpel Om Platform Company Construction Materials Sector "PT Simpel Om Unggulan" - Yayan Mulyana; Edi Hamdi (Jurnal Syntax Admiration, 2023)
The development of Indonesian commercial property (PPKom) released by the Department of Statistics of Bank Indonesia (BI) in the first quarter of 2022 welcomes 2022 as the year of revival of the Indonesian property sector. The annual performance (year on year) of the property industry sector (real estate) grew by 1.19% since the end of the COVID-19 pandemic. In addition to property growth, technological developments are increasingly facilitating and accelerating the transaction process, especially electronic shopping transactions (eCommerce). The transition of the Analog to Digital era encourages all business sectors to be more creative in mastering market competition, one of which is in the construction material supply demand sector. PT Simpel OM Unggul with the platform name "Simpel OM" is present as a material supply platform for the construction sector and a liaison between consumers and sellers with a commitment to 1x24 hour delivery and free shipping is the best solution in today's instant era. Simpel OM started marketing activities as an initial business idea in getting opportunities and markets in similar sectors. This is a general form of a linkage of the governance process with the aim of developing a business strategy in obtaining maximum achievement. Determination of goals and objectives, is the initial operational step in determining market segmentation, target consumers, and business positioning to be carried out. Taking all of that into consideration, revenue stream is the final picture that will be obtained from the running of the Company's cycle. The results of marketing analysis and planning of PT Simpel OM Unggul (Simpel OM) include segmentation, targets, positions, and marketing mix, and projected profits that will be obtained from running this business.